1996
DOI: 10.1016/s0042-6989(96)00129-0
|View full text |Cite
|
Sign up to set email alerts
|

Quinine, intracellular pH and modulation of hemi-gap junctions in catfish horizontal cells

Abstract: Quinine increases the conductance of hemi-gap junctions in horizontal cells. We investigated the mechanisms of alkalinization and the hypothesis that quinine-induced alkalinization produced these conductance increases. We found that quinine-induced alkalinizations were not blocked by cobalt, amiloride, or DIDS. Therefore, this suggests that the alkalinization is not likely due to net proton flux through opened hemi-gap channels nor is it likely due to an action on Cl-/HCO3- exchanger or Na+/H+ exchanger, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…Quinine evoked a con- centration-dependent release of ATP from C6 cells expressing connexin43, in a concentration range (50 -500 M) similar to that observed to activate connexin hemichannels (23)(24)(25). ATP concentrations measured 1 min following quinine exposure were 24, 28, and 33 M for 50, 100, and 500 mM quinine, respectively (n ϭ 8 each, p Ϫ0.012 by single factor analysis of variance).…”
Section: Low Casupporting
confidence: 59%
See 1 more Smart Citation
“…Quinine evoked a con- centration-dependent release of ATP from C6 cells expressing connexin43, in a concentration range (50 -500 M) similar to that observed to activate connexin hemichannels (23)(24)(25). ATP concentrations measured 1 min following quinine exposure were 24, 28, and 33 M for 50, 100, and 500 mM quinine, respectively (n ϭ 8 each, p Ϫ0.012 by single factor analysis of variance).…”
Section: Low Casupporting
confidence: 59%
“…Quinine has been reported to activate connexin hemichannels in multiple preparations (23)(24)(25). Quinine evoked a con- centration-dependent release of ATP from C6 cells expressing connexin43, in a concentration range (50 -500 M) similar to that observed to activate connexin hemichannels (23)(24)(25).…”
Section: Low Camentioning
confidence: 52%
“…Previous studies indicated that quinine activated putative hemichannellike currents in horizontal cells of skate and perch retina (17)(18)(19) and potentiated gap junction hemichannel currents in oocytes expressing certain connexins (e.g., Cx35) and not others (e.g., Cx43) (20). We now demonstrate in mammalian cells that quinine blocks certain types of gap junction channels in a reversible and concentration-dependent manner, whereas gap junctions formed of other connexins are unaffected.…”
supporting
confidence: 54%
“…Similar to previous reports for neurons (36,41,42), bath perfusion of 1 mM quinine increased intracellular pH, whereas NH 4 Cl withdrawal decreased intracellular pH in CHO cells (data not shown). To examine the possibility that modulation of ASICs by pH i depends on the presence of a specific ASIC subunit, we studied the effects of intracellular pH-modifying agents on the current mediated by different ASIC subunits expressed in CHO cells.…”
Section: Changing Intracellular Ph Alters Ogd-induced Injury Of Cultusupporting
confidence: 91%